Fungitoxicity of volatile constituents of some higher plants against predominant storage fungi - TIWARI, RAMESH (Indian Phytopathology, 2002)
Volatile constituents (essential oils) isolated from different parts of some higher plants were screened for their fungitoxicity by the inverted of petri plate technique at concentrations of 0.4 X 103 0.6 X 103 0.8 X-103 and 1.0 X 103 Shuo / liter against 2predominant storage fungi: from Aspergillus flavus. and A. niger isolated from the stored samples of paddy and maize grains. and Cinnamomum zeylanicum bark oil inhibited the mycelial growth of both the test fungi completely at a concentration of 0.4 X 103 Shuo / liter. None of the other oils tested showed the complete inhibition of mycelial of growth even at the highest concentration of 1.0 X 103 Shuo / liter. The oil of C. zeylanicum showed a broad range of the activity, inhibiting the mycelial growth of 29 other storage fungi completely at 0.4 X 103 Shuo / liter.